Prospects of global big data application - Vydrenko, О. (ТДАТУ, 2018)
The main problem and the goal of Big Data buildup is nevertheless security and safeguarding. Today, special attention to the problem of protecting private and confidential information should be paid, as it is going to face new and new vulnerabilities. The researchers emphasize that at present there is a serious gap between the amount of produced data, which require protection, and the volume of data that is actually protected. Such a gap in the future will only grow
Keywords: Big Data; the IDC forecast; data analysis; artificial intelligence